Rasagiline for sleep disorders in patients with Parkinson’s disease: a prospective observational study - Schettino C (Dove Medical Press, 2016)
Carla Schettino,1,2,* Clemente Dato,1,2,* Guglielmo Capaldo,1,2 Simone Sampaolo,1,2 Giuseppe Di Iorio,1,2 Mariarosa AB Melone1,2 1Department of Medical, Surgical, Neurological, Metabolic Sciences, and Aging, 2Division of Neurology and InterUniversity Center for Research in Neurosciences, Second University of Naples, Naples, Italy *These authors contributed equally to this work Introduction: Rasagiline is a selective, irreversible monoamine oxidase B inhibitor that ameliorates the symptoms of Parkinson’s disease (PD) by inhibiting striatal dopamine metabolism. There is also evidence that monoamine oxidase B inhibitors increase melatonin levels in the pineal gland and may have a beneficial effect on sleep disorders, which are a common feature in patients with PD.Methods: This single-center, prospective, observational, 12-week study compared the effect of combination therapy with levodopa 200–300 mg/d + rasagiline 1 mg/d (n=19) with levodopa 200–300 mg/d alone (n=19) in the treatment of sleep disorders in patients with idiopathic PD.Results: After 12 weeks’ treatment, mean sleep latency was significantly (P<0.001) lower and the improvement in sleep latency from baseline was significantly (P=0.001) greater in patients receiving levodopa + rasagiline than in patients receiving levodopa alone. Similarly, at the end of the study, the mean total sleep time was significantly (P=0.002) longer and the improvement from baseline in mean total sleep time was significantly (P=0.026) greater in patients receiving levodopa + rasagiline than levodopa alone. There were no significant differences between treatment groups for the mean number of awakenings reported at week 12 nor the change from baseline to week 12 in mean number of awakenings.Conclusion: Adding rasagiline to levodopa improved sleep outcomes and may be an appropriate option for patients with PD experiencing sleep disorders. Keywords: Parkinson’s disease, rasagiline, sleep disorders, Parkinson’s disease sleep scale